Role of curcumin as an antioxidant - Tarun Vyas (Wolters Kluwer Medknow Publications, 2020)
In recent years, there is an upsurge in the areas related to newer developments in prevention of diseases, especially the role of free radicals and antioxidants; free radicals are unstable chemicals formed in the body during normal metabolism or exposure to environmental toxins such as pollutants in air, food, and water. Curcumin combined with enhancing agents provides multiple health benefits. Most of these benefits can be attributed to its antioxidant and anti-inflammatory effects. Ingesting curcumin by itself does not lead to the associated health benefits due to its poor bioavailability, which appears to be primarily due to poor absorption, rapid metabolism, and rapid elimination. There are several components that can increase bioavailability. The purpose of this review is to provide a brief overview of the plethora of research regarding the health benefits of curcumin.